Special section: modeling visual word recognition (Journal of Experimental Psychology. Human Perception & Performance, 1994)
A special section on modeling visual word recognition. Topics discussed include the influences of visual, orthographic, phonological, and lexical factors on reading performance; the assumptions of the activation-verification model regarding the role of word frequency in lexical access; a dual read-out model of context effects in letter perception; the relative merits of a parallel distributed processing model and a dual-route model of naming; the regularity effect on reading aloud as a function of left-to-right phonemic position of irregularity in low-frequency exception words; a new computational model of reading aloud; the processing advantage of ambiguous words; the basic elements of a principle-based approach to model development; perception within a complex systems framework that includes resonance, attractors, subsymbols, and design principles; the assumptions that distinguish a connectionist approach to visual word recognition; and a classification of models of visual word recognition that facilitates formal comparisons between models of different formats.